Direct measurement of the unjacketed pore modulus of porous solids - Tarokh, Ali (Proc Math Phys Eng Sci, 2018)
Pressure decline caused by the extraction of oil from deep sedimentary layers depends on the pore modulus K(pp), a poroelastic parameter that characterizes the effect of pressure change on pore volume under constant mean stress. Measurement of K(pp) is difficult, however, as it requires calibration to account for fluid compressibility and compliance of the testing system. Nevertheless, knowing the easily measurable drained pore modulus K(p) and adopting an assumption on the unjacketed pore modulus K(s)″, it is possible to determine K(pp) because these pore moduli are related. Previous work on indirectly estimating K(s)″ claimed that K(s)″ is strongly dependent on Terzaghi effective pressure P′ and therefore not a constant; also, K(s)″ might be different from K(s), the solid bulk modulus of the major mineral constituent. We overcome the limitations of the indirect approach by directly measuring K(s)″. The experiments reveal that K(s)″ is indeed a constant and that for an ideal porous rock, the assumption of [Formula: see text] holds. Furthermore, a constant K(s)″ implies that K(p) and K(pp) are functions of Terzaghi effective pressure only. These results provide a framework to accurately determine the Skempton coefficient B.